Method for manufacturing hydride shielding material based on alloying precursor and shielding material
By manufacturing hydride shielding materials based on alloying precursors, the shortcomings of shielding materials in micronuclear reactors are solved, high temperature stability and neutron shielding effect are improved, and large volumes of yttrium-based hydride shielding materials can be prepared.
Patent Information
- Application Number
- CN202411535112.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
In micronuclear reactors, the commonly used metal shielding materials are insufficiently shielded. Metal hydrides are prone to hydrogen loss and cracking at high temperatures, resulting in material powdering, limiting their application as shielding structures.
By using an alloying precursor-based method, the specific steps include providing the precursor alloy, performing vacuum smelting, hot deformation and cold rolling processing, annealing, and hydrogenation at different temperatures through a sectional hydrogenation process, Reduce the risk of cracking.
The preparation of yttrium-based hydride shielding material is realized, the risk of cracking during hydrogenation is reduced, the high temperature stability and neutron shielding effect of the material are improved, and large-volume shielding materials with centimeter-level size can be manufactured.
Smart Images

Figure CN119410926A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nuclear power, and in particular relates to a method for manufacturing a hydride shielding material based on an alloying precursor and the shielding material. Background Art
[0002] With the development of the nuclear power industry, micro nuclear reactors have gained more and more attention due to their advantages of high energy density, small size, and less maintenance during operation. They have good application prospects in space, oceans, and remote areas. With the development of lightweight reactor design, the performance requirements for shielding materials are getting higher and higher. The core temperature of micro reactors is higher, and the overall volume is more compact, so the performance requirements for shielding materials are getting higher and higher. In micro reactors with limited volume, the shielding effect of commonly used metal shielding materials is insufficient; metal hydrides are prone to hydrogen loss at high temperatures, and are prone to cracking and breaking during the metal hydride process, resulting in material pulverization, which limits the application of metal hydrides as shielding structures.
[0003] Patent CN117965987A discloses a yttrium-silicon alloy material, which improves the resistance of the yttrium-based alloy to hydrogen-induced cracking in the form of fine grain strengthening by adjusting the composition of the yttrium alloy. However, the resistance of the yttrium-based alloy to cracking during the hydrogenation process is still insufficient only by adjusting the alloy composition, especially when the size of the yttrium matrix is large, it is still easy to crack during the hydrogenation process due to the unevenness of hydrogenation, resulting in difficulties in the preparation of large-sized yttrium hydride materials. Therefore, an optimized yttrium-based alloy hydrogenation method is provided, which can reduce the risk of cracking during the hydrogenation process, and has positive significance for reducing the manufacturing cost of large-sized yttrium-based hydride shielding materials. Summary of the invention
[0004] The object of the present invention is to provide a method for manufacturing a hydride shielding material based on an alloyed precursor, thereby reducing the risk of cracking of the shielding material matrix during the hydriding process. The present invention also provides a shielding material.
[0005] According to an embodiment of one aspect of the present invention, a method for manufacturing a hydride shielding material based on an alloying precursor is provided, the method comprising the following steps:
[0006] Step a): providing a precursor alloy, wherein the precursor alloy comprises 0.05%-10% Dy by weight, and the balance is Y and inevitable impurities; the precursor alloy is prepared by a vacuum melting process;
[0007] Step b): hot-deforming and cold-rolling the precursor alloy, followed by annealing to obtain an alloy blank;
[0008] Step c): removing the oxide scale of the alloy blank, heating the alloy blank to 400°C-500°C in a hydrogen atmosphere and keeping it warm for 1h-20h; then heating it to 600°C-800°C and keeping it warm for 2h-60h; then heating it to 900°C-1000°C and keeping it warm for 1h-40h; finally cooling it to 900°C and keeping it warm for 6h, cooling it to 600°C and keeping it warm for 4h, cooling it to 400°C and keeping it warm for 2h, and naturally cooling it to room temperature to obtain a finished yttrium-based hydride shielding material.
[0009] This method achieves grain refinement through precursor alloying and deformation processing. At the same time, a segmented hydrogenation process is used to perform segmented heat preservation at different temperatures during the high-temperature hydrogenation process to promote the uniform distribution of H in the metal matrix, avoid concentration gradient differences, and effectively reduce the risk of cracking during the hydrogenation process; the shielding material prepared by this method has good absorption capacity for both fast neutrons and thermal neutrons, and is stable at high temperatures and not prone to decomposition. This method can be used to prepare blocky hydride shielding materials with centimeter-level sizes.
[0010] Furthermore, in some embodiments, in step a), the precursor alloy further includes one or a combination of no more than 5.0% Si, no more than 5.0% Zr, and 5%-10% W. Si can form high melting point second phase Y5Si3 particles with Y, and Zr can form second phase Zr2Si with Si, further refining the grains and improving the oxidation resistance and high temperature resistance of the material; Zr can further improve the neutron slowing performance of the material; W has a good shielding effect on fast neutrons, and as a heavy nuclear element, it can further improve the material density and improve the photon shielding effect.
[0011] Furthermore, in some embodiments, in the step a), the precursor alloy contains 0.5%-8.0% Dy, and one or a combination of 0.05%-2.5% Si, 1.0%-2.5% Zr, 5%-10% W, and the balance is Y and unavoidable impurities.
[0012] Further, in some embodiments, in step a), the vacuum melting method is to evacuate to a temperature not exceeding 3×10 -3 Pa, heat to 1600℃-1800℃ in argon atmosphere and keep warm for at least 10min.
[0013] Furthermore, in some embodiments, in the step b), the thermal deformation includes hot pressing and / or hot rolling, wherein the temperature of the hot pressing is not less than 800°C, the temperature of the hot rolling is not less than 850°C, and the thermal deformation includes at least three processing steps.
[0014] Furthermore, in some embodiments, in the step b), the annealing temperature is 850°C-950°C.
[0015] Furthermore, in some embodiments, in step c), the heating and cooling rates are 20°C / min-40°C / min, and the hydrogen pressure is 0.1 bar-10.0 bar. By controlling the heating and cooling rates, the thermal stress during the hydrogenation process is reduced, further reducing the risk of cracking.
[0016] According to an embodiment of another aspect of the present invention, a shielding material is provided. The shielding material is manufactured using the method for manufacturing a hydride shielding material based on an alloying precursor provided in any of the aforementioned embodiments.
[0017] Furthermore, in some embodiments, the matrix of the shielding material is δ-YH2, and the atomic ratio of hydrogen to yttrium is 1.2-1.8; when the shielding material contains Si, a second phase Y5Si3 is distributed in the matrix; when the shielding material contains Zr, a second phase Zr2Si is distributed in the matrix; when the shielding material contains Si and W at the same time, a second phase Si2W is also distributed in the matrix.
[0018] Furthermore, in some embodiments, the hardness of the shielding material is not less than 90 HV. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a metallographic photograph of the alloy blank in Example 2;
[0020] Figure 2 This is a metallographic photograph of the alloy blank in Example 3;
[0021] Figure 3 is the XRD pattern of the alloy blank in Example 3;
[0022] Figure 4 is the XRD pattern of the alloy blank in Example 4;
[0023] Figure 5 is the XRD pattern of the shielding material in Example 4;
[0024] Figure 6 is the hydrogen loss temperature curve of the shielding material in Example 4;
[0025] Figure 7 This is a comparison chart of thermal neutron flux rate under thermal neutron source irradiation with different shielding states;
[0026] Figure 8 This is a comparison of neutron dose rates under thermal neutron source irradiation with different shielding conditions.
[0027] The purpose of the above drawings is to explain the present invention in detail so that those skilled in the art can understand the technical concept of the present invention, but it is not intended to limit the present invention. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0029] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The phrase appearing in various locations in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive independent or alternative embodiments. Those skilled in the art should be able to understand that the embodiments herein may be combined with other embodiments without causing structural conflicts.
[0030] In the description of this document, terms indicating orientation or positional relationships, such as "up", "down", "left", "right", "horizontal", "vertical", "height", "length", and "width", are intended to accurately describe the embodiments and simplify the description, but are not intended to limit the parts or structures involved to have a specific orientation, be installed or operate in a specific orientation, and should not be construed as a limitation on the embodiments in this document.
[0031] In the description of this article, the terms "first", "second" and the like are only used to distinguish different objects, and cannot be understood as indicating relative importance or limiting the quantity, specific order or primary and secondary relationship of the described technical features. In the description of this article, the meaning of "plurality" is at least two.
[0032] Micro-nuclear reactors can meet the flexible and diverse energy needs of the nuclear energy field due to their high energy density, small size, and low maintenance during operation. They have application prospects in space exploration, ocean fields, and energy supply in remote areas. The lightweight design of micro-reactor shielding is an important part of micro-reactor research and development, and high-performance shielding materials are the basis of lightweight shielding design. The temperature of the micro-reactor shielding environment is higher, the core structure is more complex, and the neutron flux is high, which puts higher requirements on the performance of the shielding material.
[0033] At present, there are still many deficiencies in traditional shielding materials: metal shielding materials, such as boron-containing stainless steel, dysprosium-rich aluminum-based alloys, etc., can have the function of structural shielding integration, but the neutron shielding effect is still limited, especially the slowing effect on fast neutrons is weak, and there is a problem of low solubility of elements with shielding function in the matrix, and excessive addition will affect the performance of the material; polymer organic neutron shielding materials, such as boron-containing silicone resin, lead-boron polyethylene, etc., have good neutron slowing and absorption properties, but the high temperature resistance of the organic materials currently developed is still limited, only 200-300℃, and the mechanical properties are insufficient; concrete-based composite shielding materials are low-cost and easy to construct, but they are bulky and difficult to move, and cannot meet the lightweight requirements, and cannot be used in the shielding protection of mobile nuclear reactors. Therefore, it is urgent to develop new materials for fast neutron and thermal neutron composite shielding with good shielding effect, high temperature resistance (600-900℃), and high temperature oxidation resistance.
[0034] Metal hydrides have high thermal stability, high hydrogen density, and good thermal conductivity, and have become ideal moderator materials for micro nuclear reactors. Commonly used metal hydrides include zirconium hydride, yttrium hydride, lithium hydride, titanium hydride, etc. However, metal hydrides have hydrogen loss problems at the operating temperature of nuclear reactors. Among them, the decomposition temperature of zirconium hydride and titanium hydride is about 800°C, the decomposition temperature of yttrium hydride can reach above 1000°C, and lithium hydride decomposes at about 600°C. Yttrium hydride has better thermal stability, which also shows that yttrium hydride has great potential in solving the high-temperature hydrogen loss problem of metal hydrides. However, the material is very easy to break during the hydrogenation process, and yttrium is very easy to react with nitrogen and oxygen to pulverize, resulting in material breakage.
[0035] The present invention has found that by alloying the yttrium metal matrix, its grain refinement is promoted and the oxidation resistance of the material is improved, which helps to avoid cracking during the hydrogenation process. Furthermore, the present invention has found that an important factor in the hydrogenation cracking of yttrium-based alloys is the uneven distribution of hydrogen during the hydrogenation process. By performing segmented insulation during the heating and cooling process of high-temperature hydrogenation, it is possible to promote the uniform diffusion of hydrogen in the metal matrix, avoid the occurrence of hydrogen concentration gradients in different areas of the metal matrix during the hydrogenation process, and thus realize the manufacture of centimeter-level large-volume hydride shielding materials.
[0036] An embodiment of the present invention provides a method for manufacturing a hydride shielding material based on an alloying precursor, the method comprising the following steps:
[0037] Step a): Providing a precursor alloy. The precursor alloy comprises 0.05%-10% Dy by weight, and the balance is Y and unavoidable impurities. In a preferred embodiment, the precursor alloy also contains no more than 5% Si and no more than 5% Zr.
[0038] In a further preferred embodiment, the composition of the precursor alloy is 0.5%-8.0% Dy, and one or a combination of 0.05%-2.5% Si, 1.0%-2.5% Zr, 5%-10% W, and the balance is Y and unavoidable impurities.
[0039] Y is hydrogenated to form yttrium hydride, which has excellent thermal stability, can maintain high hydrogen content at high temperature, and has good fast neutron moderation performance. The thermal neutron absorption cross section of Dy isotope can reach 1100 barn, and the thermal neutron absorption effect is excellent. Moreover, Dy has an atomic radius similar to that of Y. By adding Dy to alloy Y, the risk of cracking caused by lattice distortion can be reduced, and the forming performance of the material can be improved. Zr can refine the grains and dissolve in the matrix. Zr is hydrogenated to form zirconium hydride, which also has good fast neutron moderation ability. Si element can form a high melting point Y5Si3 second phase with Y, which can further refine the grains and improve the oxidation resistance and high temperature resistance of the material. Zr element can form a Zr2Si second phase with Si, which has a body-centered tetragonal structure, which can further improve the strength of the material, refine the grains, and improve the mechanical properties of the material; this second phase has good thermal stability, which can improve the thermal stability and oxidation resistance of the material. W is a heavy nuclear element that has a good shielding effect on fast neutrons. The addition of W can further increase the material density and improve the photon shielding effect of the material. By adding W, the shielding material can have the integrated functions of neutron slowing down, neutron absorption and photon shielding. When Si and W exist at the same time, Si2W with good thermal stability will be formed, which improves the high-temperature oxidation resistance of the material.
[0040] The precursor alloy is prepared by vacuum melting process: raw materials are prepared according to the composition ratio, and the raw materials are put into a vacuum smelting furnace and vacuumed to no more than 3×10 -3 Pa and protected by argon, heated to 1600℃-1800℃, kept warm for at least 10min to obtain alloy melt, and cast into shape.
[0041] Step b): The alloy ingot obtained in step a) is subjected to hot deformation and cold rolling, and then annealing to obtain an alloy blank. The hot deformation process includes hot pressing and / or hot rolling, the temperature of hot pressing is not less than 800°C, the temperature of hot rolling is not less than 850°C, and the hot deformation process is repeated at least three times to fully break up solidification structures such as dendrites, eliminate solidification defects such as looseness and shrinkage, and promote the uniformity of the alloy blank. The cold rolling process is performed at least three times; the annealing process is performed under argon protection, and the annealing temperature is 850°C-950°C to obtain an alloy blank with uniform fine grain structure.
[0042] Step c): remove the oxide scale of the alloy blank, then put the alloy blank into a hydrogenation furnace for hydrogenation treatment, heat the alloy blank to 400℃-500℃ in a hydrogen atmosphere of 0.1bar-10bar and keep it for 1h-20h; then heat it to 600℃-800℃ and keep it for 2h-60h; then heat it to 900℃-1000℃ and keep it for 1h-40h; finally cool it to 900℃ and keep it for 6h, cool it to 600℃ and keep it for 4h, cool it to 400℃ and keep it for 2h, and naturally cool it to room temperature, and finally obtain a yttrium-based hydride shielding material with good high-temperature stability. Among them, the heating and cooling rates are both 20℃ / min-40℃ / min, and the hydrogen pressure is 0.1bar-10.0bar.
[0043] The yttrium-based hydride shielding material prepared by the above method has a matrix of δ-YH2, and the atomic ratio of hydrogen to yttrium is 1.2-1.8. In a preferred embodiment, the shielding material contains Si, and a Y5Si3 second phase is also distributed in the matrix. In a further preferred embodiment, the shielding material contains both Si and W, and a Si2W second phase is also distributed in the matrix. The hardness of the material is not less than 90HV, and it has good fast neutron moderation performance and thermal neutron absorption performance, high hardness, good wear resistance, and can be stably used for a long time in a high temperature environment of 600℃-900℃. When the conventional heat treatment method is used to hydrogenate by constant temperature heating, when the material size does not exceed 1cm, it is easy to crack widely; and the segmented heating hydrogenation method provided in the above embodiment can manufacture a large volume of yttrium-based hydride shielding material with a size of 1cm-2cm, which has good prospects in engineering applications.
[0044] In preferred embodiment 1, a manufacturing process of a shielding material is as follows:
[0045] Step a): raw materials are provided in a weight ratio of Dy 5% and Y balance, and vacuum smelting is performed at 1700° C. for 10 minutes to obtain an alloy melt.
[0046] Step b): casting the alloy melt, hot pressing at a temperature not lower than 800°C, hot rolling at a temperature not lower than 850°C, and performing hot pressing and hot rolling for three times in total; then cold rolling for three times, and annealing at 900°C to obtain an alloy billet.
[0047] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0048] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0049] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0050] In preferred embodiment 2, a manufacturing process of a shielding material is as follows:
[0051] Step a): raw materials are provided in a weight ratio of Dy 8% and Y balance, and vacuum smelting is performed at 1700° C. for 10 minutes to obtain an alloy melt.
[0052] Step b): The alloy melt is cast into a shape, subjected to three passes of hot deformation processing, followed by three passes of cold rolling processing, and annealed at 900°C to obtain an alloy blank. The metallographic structure of the alloy blank is shown in FIG. Figure 1 As shown, it can be seen that its structure is uniform, without inclusions and defects, and its hardness is 91HV after testing.
[0053] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0054] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0055] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0056] In preferred embodiment 3, a manufacturing process of a shielding material is as follows:
[0057] Step a): providing raw materials according to a weight ratio of Dy 8%, Zr 5%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0058] Step b): Cast the alloy melt, perform three hot deformation processes, then perform three cold rolling processes, and perform annealing at 900°C to obtain an alloy blank. The grain size of the alloy blank is 50 μm-70 μm, and the microstructure hardness is 119 HV after testing. The XRD diffraction pattern of the alloy blank is as follows: Figure 3 As shown, it can be seen that the main components of the matrix are Y and Dy solid solutions, with a small amount of Zr, which plays a role in grain refinement.
[0059] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0060] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0061] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0062] In preferred embodiment 4, a manufacturing process of a shielding material is as follows:
[0063] Step a): providing raw materials according to a weight ratio of Dy 8%, Si 1%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0064] Step b): casting the alloy melt, performing three hot deformation processes, then performing three cold rolling processes, and performing annealing at 900° C. to obtain an alloy blank.
[0065] The XRD diffraction pattern of the alloy body is as follows: Figure 4 As shown, it can be seen that the main components of the matrix are Y and Dy solid solution, and there is a Y5Si3 second phase.
[0066] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0067] Keep the temperature at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep it for 1h-40h; finally, cool to 900℃ and keep it for 6h at a rate of 30℃ / min, cool to 600℃ and keep it for 4h, cool to 400℃ and keep it for 2h, stop hydrogen introduction, and cool naturally to room temperature with the furnace to obtain the finished shielding material. The XRD diffraction spectrum of the finished shielding material is as follows: Figure 5 As shown, it can be seen that after hydrogenation, the matrix of the shielding material is mainly composed of YH2 and Y5Si3.
[0068] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0069] Carry out hydrogen loss temperature measurement, Figure 6 The figure is the hydrogen loss temperature curve of YSiDy alloy hydride. The shielding material does not lose hydrogen significantly before 700°C, indicating that YSiDy alloy hydride has excellent high temperature resistance. When the temperature is higher than 700°C, YSiDy alloy hydride dehydrogenates, and the hydrogen loss rate increases rapidly after 800°C. However, the hydrogen content remains at a high level, so the material can be used in high temperature environments of 600-900°C.
[0070] In preferred embodiment 5, a manufacturing process of a shielding material is as follows:
[0071] Step a): providing raw materials according to a weight ratio of Dy 5%, Si 1%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0072] Step b): casting the alloy melt, performing three hot deformation processes, then performing three cold rolling processes, and performing annealing at 900° C. to obtain an alloy blank.
[0073] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0074] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0075] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0076] In preferred embodiment 6, a manufacturing process of a shielding material is as follows:
[0077] Step a): providing raw materials according to a weight ratio of Dy 5%, Si 0.05%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0078] Step b): casting the alloy melt, performing three hot deformation processes, then performing three cold rolling processes, and performing annealing at 900° C. to obtain an alloy blank.
[0079] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0080] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0081] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0082] In preferred embodiment 7, a manufacturing process of a shielding material is as follows:
[0083] Step a): providing raw materials according to a weight ratio of Dy 8%, Si 0.05%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0084] Step b): casting the alloy melt, performing three hot deformation processes, then performing three cold rolling processes, and performing annealing at 900° C. to obtain an alloy blank.
[0085] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0086] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0087] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0088] In preferred embodiment 8, a manufacturing process of a shielding material is as follows:
[0089] Step a): providing raw materials according to a weight ratio of Dy 8%, Si 2.5%, Zr 1.5%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0090] Step b): casting the alloy melt, performing three hot deformation processes, then performing three cold rolling processes, and performing annealing at 900° C. to obtain an alloy blank.
[0091] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0092] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0093] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0094] In preferred embodiment 9, a manufacturing process of a shielding material is as follows:
[0095] Step a): providing raw materials according to a weight ratio of Dy 8%, Si 2.5%, Zr 1%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0096] Step b): casting the alloy melt, performing three hot deformation processes, then performing three cold rolling processes, and performing annealing at 900° C. to obtain an alloy blank.
[0097] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0098] 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ for 1h-40h; finally, cool to 900℃ for 6h, 600℃ for 4h, 400℃ for 2h at a rate of 30℃ / min, stop hydrogen introduction, and cool naturally to room temperature to obtain a finished shielding material. In preferred embodiment 10, a manufacturing process of a shielding material is as follows:
[0099] Step a): providing raw materials according to a weight ratio of Dy5%, W5%, and Y balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0100] Step b): casting the alloy melt, hot pressing at a temperature not lower than 800°C, hot rolling at a temperature not lower than 850°C, and performing hot pressing and hot rolling for three times in total; then cold rolling for three times, and annealing at 900°C to obtain an alloy billet.
[0101] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0102] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0103] In preferred embodiment 11, a manufacturing process of a shielding material is as follows:
[0104] Step a): providing raw materials according to a weight ratio of Dy5%, W6%, Si2%, and Y as the balance, and vacuum melting at 1700° C. for 10 minutes to obtain an alloy melt.
[0105] Step b): casting the alloy melt, hot pressing at a temperature not lower than 800°C, hot rolling at a temperature not lower than 850°C, and performing hot pressing and hot rolling for three times in total; then cold rolling for three times, and annealing at 900°C to obtain an alloy billet.
[0106] Step c): The alloy blank is placed in a hydrogenation furnace, and heated to 400°C-500°C at a rate of 30°C / min under a hydrogenation pressure of 0.1 bar-10.0 bar and kept at this temperature for 1 h-20 h; then the temperature is raised to
[0107] Keep warm at 600℃-800℃ for 2h-60h; then heat to 900℃-1000℃ and keep warm for 1h-40h; finally, cool to 900℃ and keep warm for 6h at a rate of 30℃ / min, cool to 600℃ and keep warm for 4h, cool to 400℃ and keep warm for 2h, stop hydrogen introduction, and naturally cool to room temperature with the furnace to obtain the finished shielding material.
[0108] The finished shielding material produced by this method has a complete structure without defects such as cracks; X-ray diffraction analysis shows that the main phase of its matrix is δ-YH2. The material has good fast neutron moderation performance and thermal neutron absorption performance, and can be used as a shielding material for micro reactors such as mobile micro nuclear power units.
[0109] Under a thermal neutron source with an average energy of 0.023 MeV, the thermal neutron flux rate on the shielding material surface without shielding and after shielding with a thickness of 10 cm is as follows: Figure 7 It can be seen that compared with the unshielded state, the thermal neutron flux rate of the shielding materials provided in Example 2 (YH-8Dy), Example 3 (YH-5Zr-8Dy) and Example 3 (YH-1Si-8Dy) decreased by about three orders of magnitude after shielding, and had a good thermal neutron shielding effect.
[0110] Under a thermal neutron source with an average energy of 0.023 MeV, the neutron dose rate without shielding and after shielding with a thickness of 10 cm is as follows: Figure 8 It can be seen that compared with the shielding state, the neutron dose rate of the shielding materials provided by Example 2 (YH-8Dy), Example 3 (YH-5Zr-8Dy) and Example 3 (YH-1Si-8Dy) is significantly reduced after shielding, showing a good thermal neutron shielding effect.
[0111] The purpose of the above embodiments is to further explain the present invention in detail in conjunction with the accompanying drawings so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the present invention, the optimization or equivalent replacement of the method steps involved, and the combination of the implementation methods in different embodiments without conflict of structure and principle, all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing a hydride shielding material based on an alloying precursor, characterized in that: The following steps are involved: Step a): providing a precursor alloy, wherein the precursor alloy comprises 0.05%-10% Dy by weight, and the balance is Y and inevitable impurities; the precursor alloy is prepared by a vacuum melting process; Step b): hot-deforming and cold-rolling the precursor alloy, followed by annealing to obtain an alloy blank; Step c): removing the oxide scale of the alloy blank, heating the alloy blank to 400°C-500°C in a hydrogen atmosphere and keeping it warm for 1h-20h; then heating it to 600°C-800°C and keeping it warm for 2h-60h; then heating it to 900°C-1000°C and keeping it warm for 1h-40h; finally cooling it to 900°C and keeping it warm for 6h, cooling it to 600°C and keeping it warm for 4h, cooling it to 400°C and keeping it warm for 2h, and naturally cooling it to room temperature to obtain a finished yttrium-based hydride shielding material.
2. The method for manufacturing a hydride shielding material based on an alloying precursor according to claim 1, characterized in that: In the step a), the precursor alloy further comprises one or a combination of not more than 5.0% Si, not more than 5.0% Zr, and 5%-10% W.
3. The method for manufacturing a hydride shielding material based on an alloying precursor according to claim 2, characterized in that: In the step a), the precursor alloy contains 0.5%-8.0% Dy, and one or a combination of 0.05%-2.5% Si, 1.0%-2.5% Zr, 5%-10% W, and the balance is Y and unavoidable impurities.
4. The method for manufacturing a hydride shielding material based on an alloying precursor according to claim 1, 2 or 3, characterized in that: In the step a), the vacuum melting method is to evacuate the vacuum to a temperature not exceeding 3×10 -3 Pa, heat to 1600℃-1800℃ in argon atmosphere and keep warm for at least 10min.
5. The method for manufacturing a hydride shielding material based on an alloying precursor according to claim 1, 2 or 3, characterized in that: In the step b), the thermal deformation includes hot pressing and / or hot rolling, wherein the temperature of the hot pressing is not less than 800° C., the temperature of the hot rolling is not less than 850° C., and the thermal deformation includes at least three processing steps.
6. The method for manufacturing a hydride shielding material based on an alloying precursor according to claim 5, characterized in that: In the step b), the annealing temperature is 850°C-950°C.
7. The method for manufacturing a hydride shielding material based on an alloying precursor according to claim 1, 2 or 3, characterized in that: In the step c), the hydrogen pressure is 0.1 bar-10.0 bar, and the heating and cooling rates are 20° C. / min-40° C. / min.
8. A shielding material, characterized in that: The shielding material is manufactured by the method for manufacturing a hydride shielding material based on an alloying precursor as described in any one of claims 1 to 7.
9. The shielding material according to claim 8, characterized in that The matrix of the shielding material is δ-YH2, and the atomic ratio of hydrogen to yttrium is 1.2-1.8; when the shielding material contains Si, a second phase Y5Si3 is distributed in the matrix; when the shielding material contains Zr, a second phase Zr2Si is distributed in the matrix; when the shielding material contains both Si and W, a second phase Si2W is also distributed in the matrix.
10. The shielding material according to claim 8 or 9, characterized in that: The hardness of the shielding material is not less than 90 HV.
Citation Information
Patent Citations
High-temperature-resistant yttrium-silicon alloy material for nuclear shielding as well as preparation method and application thereof
CN117965987A